A novel variant in GATM causes idiopathic renal Fanconi syndrome and predicts progression to end‐stage kidney disease. Issue 2 (21st October 2022) - Seaby, Eleanor G.; Turner, Steven; Bunyan, David J.; Seyed‐Rezai, Fariba; Essex, Jonathan; Gilbert, Rodney D.; Ennis, Sarah
Abstract: Renal Fanconi syndrome (RFS) is a generalised disorder of the proximal convoluted tubule. Many genes have been associated with RFS including those that cause systemic disorders such as cystinosis, as well as isolated RFS. We discuss the case of a 10‐year‐old female who presented with leg pain and raised creatinine on a screening blood test. Her mother has RFS and required a kidney transplant in her thirties. Further investigations confirmed RFS in the daughter. Exome sequencing was performed on the affected mother, child, and unaffected father. We identified a novel variant in GATM ; c.965G>C p.(Arg322Pro) segregating dominantly in the mother and daughter. We validated our finding with molecular dynamics simulations and demonstrated a dynamic signature that differentiates our variant and two previously identified pathogenic variants in GATM from wildtype. Genetic testing has uncovered a novel pathogenic variant that predicts progression to end stage kidney failure and has important implications for family planning and cascade testing. We recommend that GATM is screened for in children presenting with RFS, in addition to adults, particularly with kidney failure, who may have had previous negative gene testing. Abstract : Whole exome sequencing of a mother and daughter with isolated Fanconi syndrome revealed a novel variant of GATM, c.965G>C p.(Arg322Pro). Molecular dynamic simulation confirmed that the abnormal protein product would tend to form multimers likely to disrupt mitochondrial function.